Peran Wirausaha Pertanian dalam Menghadapi Era Disrupsi Inovasi - Atika Dyah Perwita; nFN Saptana (Forum penelitian Agro Ekonomi, 2019)
Changes in strategic environment of economic globalization including disruptive innovation require agribusiness actors’ view adjustment. This paper discusses role of agri-entrepreneurs dealing with distrubictive innovation in agriculture. There are three elements of disrupsi innovation, i.e. (i) improvement levels acceptable to customer; (ii) improvement path when new agricultural commodities are introduced and refined through technological innovations; (iii) importance of different understanding between continuous and disruption innovations. Professional managers are encouraged to grow a new business expected to compete with the established ones. Agricultural business models for the upper-middle class consumers run by young entrepreneur produce new products with premium prices but the sale volume is limited. It is important to inspire young agri- entrepreneurs who accustomed to disrupted innovation to develop business based on their goals and market segments. AbstrakPerubahan lingkungan strategis berupa globalisasi ekonomi termasuk disrupsi inovasi memerlukan cara pandang baru pelaku usaha agribisnis. Tulisan ini membahas peran kewirausahaan agribisnis menghadapi era disrupsi inovasi. Ada tiga unsur disrupsi inovasi yang penting, yaitu: (i) tingkatan penyempurnaan yang dapat diterima oleh pelanggan; (2) jalur untuk penyempurnaan melalui terobosan inovasi; (iii) pemahaman yang berbeda antara inovasi berkelanjutan dan disrupsi inovasi. Para manajer profesional didorong untuk menumbuhkan bisnis baru yang dapat bersaing dengan bisnis yang telah mapan. Para wirausahawan muda menjalankan model bisnis pertanian dengan sasaran konsumen golongan ekonomi menengah-atas dengan introduksi komoditas kualitas prima dan harga premium, namun volume pasar terbatas. Implikasinya adalah perlu menyiapkan wirausaha pertanian muda yang memahami disrupsi inovasi untuk menghasilkan produk pertanian berdasarkan tujuan dan segmen pasarnya.